2013
DOI: 10.1097/mnh.0b013e32835b4889
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor, matrix regulation, and diabetic kidney disease

Abstract: Recent publications implicate CCN-2 as both an evolving marker and mediator of diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 86 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…The interactions lead to the activation of intracellular signaling pathways and the activation of transcription factors triggered inflammatory mediators and growth factors release. These in turn mediated extracellular matrix (ECM) protein accumulation, vessel permeability alteration, and proteinuria [6, 7]. Previous treatment of DN focused on aggressive control of hyperglycemia and blood pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions lead to the activation of intracellular signaling pathways and the activation of transcription factors triggered inflammatory mediators and growth factors release. These in turn mediated extracellular matrix (ECM) protein accumulation, vessel permeability alteration, and proteinuria [6, 7]. Previous treatment of DN focused on aggressive control of hyperglycemia and blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous treatment of DN focused on aggressive control of hyperglycemia and blood pressure. Currently, glucose-dependent pathways emerged as an important strategy to retard the progression of DN [6]. Several in vitro and in vivo studies have shown DN amelioration by managing the hyperglycemia-induced oxidative stress, inflammation, and lipid accumulation [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CTGF is able to interact with receptors on cells, including integrins, tyrosine receptor kinase A, lowdensity lipoprotein receptor-related protein (LRP), and heparan sulfate proteoglycans [115]. It has pro-inflammatory functions and it may mediate diabetic nephropathy pathogenesis [116]. In a study on streptozotocin (STZ)-induced diabetic C57BL/6J mice and type 2 diabetic ob/ob mice, CTGF levels in the blood and urine were increased in these diabetic mice.…”
Section: Ccn Family Proteins In Obesity and Associated Diseasesmentioning
confidence: 98%
“…22,23 Its overproduction was proposed to play a major role in many fibrotic diseases, including renal fibrosis. 24,25 Ito 26 first studied pathogenic role of CTGF in DN and found that its expression was correlated with the severity and progression of kidney injury. Using transgenic mice, Yokoi et al 27 provided direct evidence of CTGF in the pathogenesis of DN, especially in podocytes injury.…”
Section: Discussionmentioning
confidence: 99%